Limit theorems for solutions of multipoint boundary-value problems with a parameter in Sobolev spaces - Atlasiuk , O. M. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.927 We consider the most general class of multipoint boundary-value problems for systems of linear ordinary differential equations of an arbitrary order whose solutions belong to the given Sobolev space W_p^n+r, with n≥ 0, r≥ 1, and 1≤ p≤ ∞. We establish constructive sufficient conditions under which the solutions of these problems are continuous with respect to the parameter ε at ε=0 in the space W_p^n+r.